2018
DOI: 10.1590/s0100-83582017350100087
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Performance of Glyphosate Resistant and Glyphosate Susceptible Hairy Fleabane under Light Intensity

Abstract: -Herbicide resistance can confer lower competitive abilities; however scarse information is available about the photosynthetic performance between glyphosate-resistant and -susceptible hairy fleabane biotypes coming from areas with similar weed management history. Thus, the goal was to evaluate the photosynthetic performance under different light intensities between glyphosateresistant and -susceptible hairy fleabane biotypes, from RR soybean fields with a similar weed management history. The tested factors we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Vivancos et al [71] observed that photosynthesis is unaffected by glyphosate in tolerant soybeans, whereas it is rapidly inhibited in sensitive genotypes subjected to glyphosate treatment. The photosynthetic parameters of the herbicide-tolerant genotype are superior to those of the sensitive genotype of hairy fleabane [72]. The bentazone-tolerant cultivar Williams 82 exhibits symptoms 1 DAT but rapidly recovered 2 DAT [7,16].…”
Section: Discussionmentioning
confidence: 98%
“…Vivancos et al [71] observed that photosynthesis is unaffected by glyphosate in tolerant soybeans, whereas it is rapidly inhibited in sensitive genotypes subjected to glyphosate treatment. The photosynthetic parameters of the herbicide-tolerant genotype are superior to those of the sensitive genotype of hairy fleabane [72]. The bentazone-tolerant cultivar Williams 82 exhibits symptoms 1 DAT but rapidly recovered 2 DAT [7,16].…”
Section: Discussionmentioning
confidence: 98%
“…Evaluation of photosynthetic parameters in herbicide-resistant plants makes it possible to verify the changes that occur in photosynthetic metabolism, one of which is stomatal conductance [6]. Stomatal conductance was further understood as a physiological mechanism to control transpiration, which plays a role in water absorption, nutrition and leaf temperature regulation [26].…”
Section: Physiological Activity Test On Resistant Weedsmentioning
confidence: 99%
“…The herbicide application causes differences in physiological activity that occurs between resistant and sensitive weeds [6]. The plant metabolism process was correlated with gas exchange that occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The method of graphical analysis of relative productivity (RP) (Radosevich et al 2007;Cousens 1991) was used for analyzing data on HEI, LA and SDW, as described by Ruchel et al (2019) and Silva et al (2017). The criterion to consider the existence of differences in competitive ability, regarding indexes of relative competitiveness (RC), coefficient of relative clustering (K) and coefficient of competitiveness (C), calculated in the 50:50 proportion, was that the T-test should show differences in at least two of them (Bianchi et al 2006).…”
Section: Glycine Max Amaranthus Viridi Competitivitymentioning
confidence: 99%